2014
DOI: 10.3732/ajb.1300279
|View full text |Cite
|
Sign up to set email alerts
|

Gisekia (Gisekiaceae): Phylogenetic relationships, biogeography, and ecophysiology of a poorly known C4 lineage in the Caryophyllales

Abstract: Gisekia represents an isolated C4 lineage within core Caryophyllales dating back to the Miocene Epoch and probably spread along the African arid corridor from a South African center of origin. The seven currently recognized species should be treated as one polymorphic species or species complex, Gisekia pharnaceoides agg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In APG III (), these included Barbeuiaceae, Gisekiaceae, Lophiocarpaceae and Stegnospermataceae. Most recent studies (Brockington et al ., , ; Bissinger et al ., ) have found that subfamily Rivinoideae of Phytolacaccaeae are sister to Nyctaginaceae, and we propose here to accept them at the family level (Petiveriaceae, including Rivinaceae) to maintain the previous use of family names in this larger clade. The priority of Petiveriaceae C.Agardh 1824 over Rivinaceae C.Agardh 1824 was established by Meisner (), who combined the tribes Rivineae Dumort.…”
Section: Superasteridsmentioning
confidence: 77%
“…In APG III (), these included Barbeuiaceae, Gisekiaceae, Lophiocarpaceae and Stegnospermataceae. Most recent studies (Brockington et al ., , ; Bissinger et al ., ) have found that subfamily Rivinoideae of Phytolacaccaeae are sister to Nyctaginaceae, and we propose here to accept them at the family level (Petiveriaceae, including Rivinaceae) to maintain the previous use of family names in this larger clade. The priority of Petiveriaceae C.Agardh 1824 over Rivinaceae C.Agardh 1824 was established by Meisner (), who combined the tribes Rivineae Dumort.…”
Section: Superasteridsmentioning
confidence: 77%
“…Family delimitation of the clade that includes Phytolaccaceae and Nyctaginaceae is still unclear. Most recent studies (Brockington et al ., ; Bissinger et al ., ) found Gisekia L. (formerly in Phytolaccaceae or Molluginaceae) to be sister to a clade with Nyctaginaceae, Phytolaccaceae and Sarcobataceae. Furthermore Phytolaccaceae were found to be paraphyletic, with Rivinoideae sister to Nyctaginaceae instead of the rest of Phytolaccaceae, which could result in the recognition of Rivinaceae as separate from Phytolaccaceae.…”
Section: Resultsmentioning
confidence: 99%
“…Kuntze, Delosperma cooperi L. Bolus). Furthermore, Phytolacca dioica L. (Phytolaccaceae) was used as an outgroup according to the results of Christin et al (2011) and Bissinger et al (2014). Table 1 presents sequences generated for this study and downloaded accessions from GenBank (www.ncbi.nlm.nih.gov/genbank/).…”
Section: Sequencing and Phylogenetic Inferencementioning
confidence: 99%